2022
DOI: 10.3233/jad-215368
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Dementia Caused by Cardiovascular Disease in Australia

Abstract: Background: The established link between cardiovascular disease (CVD) and dementia may provide new insights into dementia prevention. Objective: It aims to quantify the burden of dementia attributable to people with CVD. Methods: A Markov microsimulation model was developed to simulate the lifetime cost and quality-adjusted life-years (QALYs) related to people with and without CVD in Australia. A de-novo systematic review was undertaken to identify all evidence around the association between CVD [i.e., stroke,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The re‐implementation of the Banned Drinker Register (BDR) in the NT offers a unique opportunity to assess the secondary impact of alcohol policy on child and adolescent assault victimisation and perpetration. The NT has the highest rate of alcohol consumption and alcohol‐related deaths in Australia, and in response, has implemented a wide variety of both community and Territory wide alcohol policies [19, 20]. The NT government passed the Alcohol Harm Reduction Act [21] with the aim of addressing the high level of alcohol‐related harm across the NT.…”
Section: Introductionmentioning
confidence: 99%
“…The re‐implementation of the Banned Drinker Register (BDR) in the NT offers a unique opportunity to assess the secondary impact of alcohol policy on child and adolescent assault victimisation and perpetration. The NT has the highest rate of alcohol consumption and alcohol‐related deaths in Australia, and in response, has implemented a wide variety of both community and Territory wide alcohol policies [19, 20]. The NT government passed the Alcohol Harm Reduction Act [21] with the aim of addressing the high level of alcohol‐related harm across the NT.…”
Section: Introductionmentioning
confidence: 99%
“…1 People with CVD contribute to increases in the cost burden of dementia. 2 Evidence suggests dementia in advanced age develops after a lifelong sequence of events, beginning with exposure to vascular risk factors in youth, followed by heart diseases. 3 A recent retrospective cohort study of predominantly younger adults found CVD diagnosis increased the risk of dementia by 17%.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) and dementia are two co‐existing age‐related chronic conditions that contribute to disease burden in older adults 1 . People with CVD contribute to increases in the cost burden of dementia 2 . Evidence suggests dementia in advanced age develops after a lifelong sequence of events, beginning with exposure to vascular risk factors in youth, followed by heart diseases 3 .…”
Section: Introductionmentioning
confidence: 99%